Interventions for reducing medication errors in children in hospital - Maaskant, Jolanda M.; Vermeulen, Hester; Apampa, Bugewa; Fernando, Bernard; Ghaleb, Maisoon A.; Neubert, Antje; Thayyil, Sudhin; Soe, Aung (Cochrane Database of Systematic Reviews, 2015)
Many hospitalised patients are affected by medication errors (MEs) that may cause discomfort, harm and even death. Children are at especially high risk of harm as the result of MEs because such errors are potentially more hazardous to them than to adults. Until now, interventions to reduce MEs have led to only limited improvements.To determine the effectiveness of interventions aimed at reducing MEs and related harm in hospitalised children.The Effective Practice and Organisation of Care Group (EPOC) Trials Search Co-ordinator searched the following sources for primary studies: The Cochrane Library, including the Cochrane Central Register of Controlled Trials (CENTRAL), the Economic Evaluation Database (EED) and the Health Technology Assessments (HTA) database; MEDLINE, EMBASE, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Proquest Dissertations & Theses, Web of Science (citation indexes and conference proceedings) and the EPOC Register of Studies. Related reviews were identified by searching the Cochrane Database of Systematic Reviews and the Database of Abstracts of Reviews of Effects (DARE). Review authors searched grey literature sources and trial registries. They handsearched selected journals, contacted researchers in the field and scanned reference lists of relevant reviews. They conducted searches in November 2013 and November 2014. They applied neither language nor date limits.Randomised controlled trials, controlled before-after studies and interrupted time series investigating interventions to improve medication safety in hospitalised children (<= 18 years). Participants were healthcare professionals authorised to prescribe, dispense or administer medications. Outcome measures included MEs, (potential) patient harm, resource utilisation and unintended consequences of the interventions.Two review authors independently selected studies, extracted data and assessed study quality using the EPOC data collection checklist. We evaluated the risk of bias of included studies and used the GRADE (Grades of Recommendation, Assessment, Development and Evaluation) approach to assess the quality of the body of evidence. We described results narratively and presented them using GRADE tables.We included seven studies describing five different interventions: participation of a clinical pharmacist in a clinical team (n = 2), introduction of a computerised physician order entry system (n = 2), implementation of a barcode medication administration system (n = 1), use of a structured prescribing form (n = 1) and implementation of a check and control checklist in combination with feedback (n = 1).Clinical and methodological heterogeneity between studies precluded meta-analyses. Although some interventions described in this review show a decrease in MEs, the results are not consistent, and none of the studies resulted in a significant reduction in patient harm. Based on the GRADE approach, the overall quality and strengfh of the evidence are low.Current evidence on effective interventions to prevent MEs in a paediatric population in hospital is limited. Comparative studies with robust study designs are needed to investigate interventions including components that focus on specific paediatric safety issues.
EVALuna2:18941